A Weak Bargaining Set for Contract Choice Problems - Somdeb Lahiri (Fondazione Eni Enrico Mattei (FEEM), 2006)
In this paper, we consider the problem of choosing a set of multi-party contracts, where each coalition of agents has a non-empty finite set of feasible contracts to choose from. We call such problems, contract choice problems. The main result of this paper states that every contract choice problem has a non-empty weak bargaining set. The need for such a solution concept which is considerably weaker than the core arises, since it is well known that even for very simple contract choice problems, the core may be empty. We also show by means of an example that the bargaining set due to Mas-Colell (1989), as well as a weaker version of it, may be empty for contract choice problems, thereby implying that the weakening we suggest is in some ways tight
Keywords: C78; D71; 330; Weak bargaining set; Contract choice; NTU game; Matching; Vertragstheorie; Verhandlungstheorie; Matching